Micro-nano hierarchical pore bearing retainer as well as preparation method and application thereof
By introducing nanopores into the porous polyimide cage, the pore structure is optimized, the problem of excessive oil output rate is solved, the oil retention rate is significantly improved, and it is suitable for high-speed bearings and stable and continuous lubrication is achieved.
Patent Information
- Application Number
- CN202411803757.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing porous polyimide cages have too fast oil output when the bearing speed increases, causing the lubricant to be thrown out in a short time, reducing the oil supply life of the bearing cage and are not suitable for high-speed bearings.
By introducing nanopores on the basis of micron-scale porous polyimide cages, the pore structure is optimized and the capillary effect of oil is improved, thereby reducing excessive oil output. The specific method includes soaking in a polar organic solvent, performing a second soaking in a carbon dioxide fluid, and performing high temperature treatment to produce a nanopore structure.
It significantly improves the oil retention rate of the porous cage at high speed, extends the oil supply life, is suitable for high-speed bearings, and achieves stable and continuous lubrication.
Smart Images

Figure CN119529377A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cage modification, and in particular to a micro-nano multi-level hole bearing cage and a preparation method and application thereof. Background Art
[0002] The porous bearing cage was first used in ball bearings in the 1960s. It can not only isolate the ball bodies from each other, but also store lubricating oil through its internal pore structure. When the bearing is running at high speed, the lubricating oil seeps out of the holes under the action of centrifugal force to participate in the interface lubrication between the rolling body and the cage. Once the operation stops, the lubricating oil thrown out by the centrifuge is sucked back into the porous cage under the action of capillary action and stored, and thrown out again for lubrication during subsequent operation. This realizes the long-life maintenance-free oil supply of the bearing cage without the need for external oil supply equipment. It is suitable for occasions where it is inconvenient to add lubricating oil and oil leakage is not allowed, such as high-end equipment fields such as aviation and aerospace.
[0003] The porous polyimide oil-containing cage has the advantages of the superior mechanical properties of polyimide as well as excellent chemical, thermal and dimensional stability and the strong porosity adjustability of polymers. However, when the bearing speed gradually increases, the oil outflow rate of the porous polyimide cage is too fast, causing the lubricating oil to be thrown out from the inside of the cage in a short time, reducing the oil supply life of the bearing cage, and is not suitable for high-speed bearings. Summary of the invention
[0004] The object of the present invention is to provide a micro-nano multi-level porous polyimide cage and its preparation method and application. Compared with ordinary porous polyimide cages, the micro-nano multi-level porous polyimide cage provided by the present invention has significantly improved oil retention rate at high speed, long oil supply life, and is suitable for high-speed bearings.
[0005] The oil retention rate of the porous cage can be significantly improved.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides a micro-nano multi-level porous polyimide retainer, comprising mutually interpenetrating micrometer holes and nanometer holes; the average pore size of the micrometer holes is 1-3 μm, and the average pore size of the nanometer holes is 6-40 nm.
[0008] Preferably, the porosity of the micro-nano multi-level porous polyimide retainer is 10-40%.
[0009] The present invention provides a method for preparing the micro-nano multi-level porous polyimide retainer described in the above scheme, comprising the following steps:
[0010] The micron-sized porous polyimide cage is first immersed in a polar organic solvent to obtain a softened micron-sized porous polyimide cage;
[0011] placing the softened micron-sized porous polyimide retainer in a carbon dioxide fluid environment for a second soaking, so that the carbon dioxide is dissolved in the retainer, thereby obtaining a micron-sized porous polyimide retainer in which carbon dioxide is dissolved;
[0012] The micron-scale porous polyimide retainer with dissolved carbon dioxide is subjected to high-temperature treatment, the carbon dioxide gas expands to produce a nanoporous structure, and then cooled to obtain the micro-nano multi-level porous polyimide retainer; the temperature of the high-temperature treatment is 80-270°C.
[0013] Preferably, the second immersion temperature is 20-70° C., the pressure is 8-30 MPa, and the time is 0.5-72 h.
[0014] Preferably, the high temperature treatment time is 10 to 120 seconds.
[0015] Preferably, the polar organic solvent is one or more of N-methyl-2-pyrrolidone, dimethyl sulfoxide and N-N-dimethylacetamide.
[0016] Preferably, the first immersion temperature is 25-150° C. and the time is 0.1-5 h.
[0017] Preferably, the average pore size of the micron-sized porous polyimide retainer is 1 to 3 μm.
[0018] Preferably, before the first soaking, the method further includes washing and drying the micron-sized porous polyimide retainer.
[0019] The present invention provides the use of the micro-nano multi-stage porous polyimide cage described in the above scheme or the micro-nano multi-stage porous polyimide cage prepared by the preparation method described in the above scheme in a low-speed bearing or a high-speed bearing.
[0020] The invention provides a micro-nano multi-level porous polyimide retainer, comprising mutually interpenetrating micrometer holes and nanometer holes; the average pore size of the micrometer holes is 1-3 μm, and the average pore size of the nanometer holes is 6-40 nm.
[0021] The pore size of the existing porous polyimide retainer is micrometer-sized, and the size is relatively large. When the bearing speed gradually increases, the oil flow rate is too fast, causing the lubricating oil to be thrown out from the inside of the retainer in a short time, reducing the oil supply life of the bearing retainer. The present invention introduces nanopores on the basis of micrometer-sized pores. The nanopores can improve the capillary action of the oil, thereby reducing the excessive oil flow when the bearing speed increases, and the larger micrometer pore size is conducive to the storage and release of the oil. The present invention significantly improves the oil retention rate under variable centrifugal force conditions without losing the oil content (which determines the service life of the equipment) by optimizing the pore structure. This can effectively prevent the loss of lubricating oil, achieve stable and continuous lubrication, meet the needs of modern industry for long-term lubrication, and has excellent performance and broad application prospects.
[0022] Compared with micron-scale porous polyimide cages, micro-nano multi-level porous polyimide (GPPI) cages have stronger adaptability under different centrifugal force conditions, higher oil retention rate, and have the advantages of strong environmental and internal interconnectivity, low surface energy, large specific surface area, and high mass transfer efficiency.
[0023] The present invention provides a method for preparing the micro-nano multi-level porous polyimide cage described in the above scheme, which is first soaked in a polar organic solvent for softening, then soaked in a carbon dioxide fluid for a second time, and then subjected to high temperature treatment, thereby successfully introducing new nano-level pores on the basis of maintaining the original micron pores and dimensional stability of the porous cage. The method provided by the present invention is suitable for commercial porous polyimide cages. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the average pore size of the PPI cage in Example 1;
[0025] Figure 2 Schematic diagram of the advance and retreat mercury curve of the PPI cage in Example 1;
[0026] Figure 3 Dimensional comparison diagram of the PPI cage and the GPPI cage in Example 1;
[0027] Figure 4 This is a cross-sectional SEM image of the GPPI cage in Example 1;
[0028] Figure 5 This is a comparison of optical photographs of the PPI cage and the GPPI cage in Example 1;
[0029] Figure 6 The oil content comparison diagram of the PPI cage and the GPPI cage in Example 1;
[0030] Figure 7It is a comparison diagram of the oil retention rate of the PPI cage and the GPPI cage at different speeds in Example 1;
[0031] Figure 8 The oil retention rate comparison diagram of the PPI cage and the GPPI cage at different times at 10000r / min in Example 1;
[0032] Fig. 9 The oil content comparison diagram of the PPI cage and the GPPI cage in Example 2;
[0033] Fig.10 It is a comparison diagram of the oil retention rate of the PPI cage and the GPPI cage at different speeds in Example 2;
[0034] Fig.11 The figure is a comparison chart of the oil retention rates of the PPI cage and the GPPI cage in Example 1 at different times at 3000 r / min. DETAILED DESCRIPTION
[0035] The invention provides a micro-nano multi-level porous polyimide retainer, comprising mutually interpenetrating micrometer holes and nanometer holes; the average pore size of the micrometer holes is 1-3 μm, and the average pore size of the nanometer holes is 6-40 nm.
[0036] In a specific embodiment, the average pore size of the micropores may be 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm; the average pore size of the nanopores may be 6 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm or 40 nm.
[0037] In the present invention, the porosity of the micro-nano multi-level porous polyimide retainer is preferably 10-40%. In a specific embodiment, it can be 10%, 15%, 20%, 25%, 30%, 35% or 40%.
[0038] The present invention introduces nanopores on the basis of micron-scale pores. Nanopores can improve the capillary action of oil, thereby reducing the excessive oil discharge when the bearing speed increases, while the larger micron pore size is conducive to the storage and release of oil. The present invention significantly improves the oil retention rate under variable centrifugal force conditions without losing the oil content (determining the service life of the equipment) by optimizing the pore structure. This can effectively prevent the loss of lubricating oil, achieve stable and continuous lubrication, meet the needs of modern industry for long-term lubrication, and has excellent performance and broad application prospects.
[0039] The present invention provides a method for preparing the micro-nano multi-level porous polyimide retainer described in the above scheme, comprising the following steps:
[0040] The micron-sized porous polyimide cage is first immersed in a polar organic solvent to obtain a softened micron-sized porous polyimide cage;
[0041] placing the softened micron-sized porous polyimide retainer in a carbon dioxide fluid environment for a second soaking, so that the carbon dioxide is dissolved in the retainer, thereby obtaining a micron-sized porous polyimide retainer in which carbon dioxide is dissolved;
[0042] The micron-scale porous polyimide retainer with dissolved carbon dioxide is subjected to high-temperature treatment, the carbon dioxide gas expands to produce a nanoporous structure, and then cooled to obtain the micro-nano multi-level porous polyimide retainer; the temperature of the high-temperature treatment is 80-270°C.
[0043] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0044] The present invention conducts a first immersion of the micron-sized porous polyimide retainer in a polar organic solvent to obtain a softened micron-sized porous polyimide retainer.
[0045] In the present invention, the average pore size of the micron-sized porous polyimide retainer is preferably 1-3 μm; the micron-sized porous polyimide retainer can be a commercially available product or can be prepared using a process well known in the art.
[0046] Before the first soaking, the present invention preferably washes and dries the micron-sized porous polyimide holder. The present invention has no special requirements for the washing, as long as the grease and impurities on the surface of the micron-sized porous polyimide holder can be removed; for example, petroleum ether, acetone and ethanol can be used for washing respectively.
[0047] In the present invention, the polar organic solvent is preferably one or more of N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO) and N-dimethylacetamide (DMAC). The present invention has no special requirements on the amount of the polar organic solvent, as long as it can immerse the micron-sized porous polyimide holder.
[0048] In the present invention, the temperature of the first immersion is preferably 25-150°C, and the time is preferably 0.1-5h; in a specific embodiment, the temperature of the first immersion can be 25°C, 40°C, 60°C, 80°C, 100°C, 120°C, 130°C, 140°C or 150°C; the time of the first immersion can be 0.1h, 0.5h, 1h, 2h, 3h, 4h or 5h.
[0049] The present invention softens the micron-level porous polyimide retainer through the first immersion, so as to facilitate the subsequent dissolution of carbon dioxide into the retainer.
[0050] After obtaining the softened micron-sized porous polyimide retainer, the present invention places the softened micron-sized porous polyimide retainer in a carbon dioxide fluid environment for a second soaking to dissolve the carbon dioxide in the retainer, thereby obtaining the micron-sized porous polyimide retainer in which carbon dioxide is dissolved.
[0051] In the present invention, the temperature of the second immersion is preferably 20-70°C, the pressure is preferably 8-30MPa, and the time is preferably 0.5-72h; in a specific embodiment, the temperature of the second immersion can be 20°C, 30°C, 40°C, 50°C, 60°C or 70°C, the pressure of the second immersion can be 8MPa, 10MPa, 15MPa, 20MPa, 25MPa or 30MPa, and the time of the second immersion can be 0.5h, 5h, 10h, 15h, 20h, 30h, 40h, 50h, 60h, 65h or 72h.
[0052] The present invention dissolves carbon dioxide into the softened micron-sized porous polyimide retainer through the second soaking.
[0053] After obtaining the micron-sized porous polyimide retainer with dissolved carbon dioxide, the present invention performs high-temperature treatment on the micron-sized porous polyimide retainer with dissolved carbon dioxide, expands the carbon dioxide gas to generate a nanoporous structure, and cools the micro-nano multi-stage porous polyimide retainer.
[0054] In the present invention, the temperature of the high temperature treatment is 80-270°C, and the time of the high temperature treatment is preferably 10-120s; in a specific embodiment, the temperature of the high temperature treatment can be 80°C, 100°C, 130°C, 150°C, 170°C, 200°C, 240°C or 270°C, and the time of the high temperature treatment can be 10s, 30s, 50s, 70s, 90s, 110s or 120s. In the present invention, the high temperature treatment can be carried out in an oil bath or in an oven. The present invention does not make special requirements for this, as long as a high temperature environment can be provided.
[0055] The present invention promotes the expansion of carbon dioxide gas to generate nanopores through high temperature treatment. Since the porous polyimide retainer has excellent thermal stability, the expansion of carbon dioxide gas is limited. Therefore, the present invention can maintain the original micron pores of the porous retainer and only form nanometer-sized pores.
[0056] In the present invention, the cooling temperature is preferably 1 to 5°C, and the time is preferably 3 min to 5 h. In a specific embodiment, the cooling temperature can be 1°C, 3°C or 5°C, and the rapid cooling time can be 5 min, 10 min, 30 min, 1 h, 2 h, 3 h, 4 h or 5 h. The present invention shapes the pores by cooling.
[0057] After the cooling is completed, the present invention preferably washes the cooled retaining frame, and the washing detergent is preferably petroleum ether.
[0058] The present invention provides the use of the micro-nano multi-stage porous polyimide cage described in the above scheme or the micro-nano multi-stage porous polyimide cage prepared by the preparation method described in the above scheme in a low-speed bearing or a high-speed bearing.
[0059] When the bearing speed gradually increases, the oil outflow rate of the micron-sized porous polyimide cage is too fast, causing the lubricating oil to be thrown out from the inside of the cage in a short time, which is not suitable for high-speed bearings. The present invention introduces nanopores, which can improve the capillary effect of the oil, thereby reducing the excessive oil outflow when the bearing speed increases, while the larger micron pore size is conducive to the storage and release of the oil. Therefore, the present invention is not only suitable for low-speed bearings, but also for high-speed bearings.
[0060] The micro-nano multi-level hole retainer provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0061] Example 1
[0062] (1) The porosity of the micron-sized porous polyimide (PPI) cage used is 18% and the average pore size is 1.05 μm. Figure 1 and Figure 2 As shown, the interior of the micron-scale porous polyimide retainer is an interconnected porous structure that facilitates the storage of lubricating oil.
[0063] (2) The clean and dried porous polyimide retainer is placed in NMP solvent for a first soaking, the temperature is maintained at 80° C., and the time is 1 hour to obtain a softened micron-sized porous polyimide retainer.
[0064] (3) The softened micron-sized porous polyimide retainer is transferred to a supercritical carbon dioxide fluid environment for a second immersion at an ambient temperature of 35° C., a pressure of 9 MPa, and a time of 2 h to obtain a micron-sized porous polyimide retainer in which carbon dioxide is dissolved.
[0065] (4) The obtained micron-scale porous polyimide retainer with dissolved carbon dioxide was first transferred to a high temperature environment and treated at 120°C for 30 seconds, and then transferred to an ice bath at 5°C for cooling for 10 minutes to induce carbon dioxide gas nucleation and growth until the pores were fixed, thereby obtaining a micro-nano multi-level porous polyimide (denoted as GPPI) retainer with a porosity of 19.1%.
[0066] The cross-sectional morphology of the obtained GPPI cage is as follows: Figure 4 shown. Figure 4 In the figure, (a) is a cross-sectional morphology at a scale of 10 μm, (b) is an enlarged view of the rectangular frame in (a), and (c) is an enlarged view of the rectangular frame in (b). Figure 4 It can be seen that the cage has pore structures of different sizes and is still a through structure, which is conducive to the storage of lubricating oil.
[0067] The dimensions of the PPI cage and GPPI cage were tested and calculated using an optical microscope, such as Figure 3 and Figure 5 As shown, Figure 5 The left side is the PPI cage, and the right side is the GPPI cage. Figure 3 and Figure 5 It can be seen that the inner diameter of the PPI cage is 4.41 mm, the outer diameter is 5.47 mm, and the thickness is 0.53 mm; the inner diameter of the GPPI cage is 4.41 mm, the outer diameter is 5.47 mm, and the thickness is 0.53 mm. This shows that the method provided by the present invention can maintain the dimensional stability of the cage components.
[0068] Test Example 1
[0069] The PPI cage and GPPI cage in Example 1 were placed in a vacuum oil immersion box for 24 hours to obtain sufficient PAO10 lubricating oil. The vacuum degree was 0.08MPa, the temperature was 100℃, and the time was 24 hours. The oil content was 7.81% (PPI cage) and 8.13% (GPPI cage), respectively. Figure 6 shown.
[0070] The oil retention rate of PPI cage and GPPI cage at different speeds for 10 minutes is as follows Figure 7 The corresponding specific data are shown in Table 1; the oil retention rate at different times at 10000r / min is as follows Figure 8 As shown, the corresponding specific data are shown in Table 2. The data units in Table 1 and Table 2 are %.
[0071] Table 1 Oil retention rate of cage at different speeds in Example 1 (PAO10 lubricant)
[0072] 3000r / min 5000r / min 7000r / min 9000r / min 10000r / min PPI cage 97.96 95.92 95.92 93.87 89.8 GPPI Cage 96.97 100 100 96.21 94.7
[0073] Table 2 Oil retention rate of the cage at different times at 10000r / min in Example 1 (PAO10 lubricating oil)
[0074] 0min 10min 20min 30min 40min PPI cage 100 89.8 88.43 83.67 79.59 GPPI Cage 100 94.7 93.94 93.94 93.94
[0075] Depend on Figure 7From Table 1, it can be seen that when the speed is increased to 10000r / min, the oil retention rate of the GPPI cage remains at 94.7%, while the oil retention rate of the PPI cage drops to 89.80%. Figure 8 As shown in Table 2, after 40 minutes of rotation at 10000 r / min, the oil retention rate of the GPPI cage is still higher than 93%, while that of the PPI cage drops to 80%.
[0076] In the present invention, the oil content is calculated according to Formula 1, and the oil retention rate is calculated according to Formula 2:
[0077]
[0078] In formula 1 and formula 2, m1, m0 and m i They represent the initial mass of the cage, the mass after being filled with lubricating oil, and the mass after the i-th centrifuge oil removal.
[0079] Test Example 2
[0080] The PAO10 lubricant in Test Example 1 was replaced with PAO4 lubricant, and the other test conditions were the same as those in Test Example 1. The test results are shown in Tables 3 and 4. The data units in Tables 3 and 4 are %.
[0081] Table 3 Oil retention rate of cage at different speeds in Example 1 (PAO4 lubricant)
[0082] 3000r / min 5000r / min 7000r / min 9000r / min 10000r / min PPI cage 96.93 95.22 94.52 93.07 90.00 GPPI Cage 96.26 100 99.46 95.47 95.06
[0083] Table 4 Oil retention rate of the cage at different times at 10000r / min in Example 1 (PAO4 lubricant)
[0084]
[0085]
[0086] The test results show that the oil content of the PPI cage and the GPPI cage are 7.90% and 8.31% respectively. After 10000r / min for 10min, the oil retention rate of the GPPI cage is 95.06%, and the oil retention rate of the PPI cage is 90.00%. After 40min at 10000r / min, the oil retention rate of the GPPI cage is still 90%, while that of the PPI cage drops to 79%.
[0087] Example 2
[0088] The GPPI cage was prepared in the same manner as in Example 1, except that in step (1), the porosity of the PPI cage was 29% and the pore size was 2.54 μm; the remaining steps were the same as in Example 1.
[0089] The results show that the dimensions of the GPPI cage remain stable.
[0090] Test Example 3
[0091] The PPI cage and GPPI cage in Example 2 were placed in a vacuum oil immersion box for 24 hours to obtain sufficient PAO10 lubricating oil. The vacuum degree was 0.08MPa, the temperature was 100°C, and the time was 24 hours. The oil content of the PPI cage and the GPPI cage were 19.22% and 19.43%, respectively. Fig. 9 .
[0092] The oil retention rate of the PPI cage and GPPI cage after being swung for 10 minutes at 1000r / min, 2000r / min and 3000r / min is tested. The results are as follows Fig.10 As shown, Fig.10 The corresponding specific data are shown in Table 5. After 60 minutes of shaking at 3000r / min, the oil retention rate of the PPI cage and GPPI cage is shown in Fig.11 The corresponding specific data are shown in Table 6. The data units in Table 5 and Table 6 are %.
[0093] Table 5 Oil retention rate of cage at different speeds in Example 2 (PAO10 lubricant)
[0094] 1000r / min 2000r / min 3000r / min PPI cage 98.21 97.93 94.42 GPPI Cage 98.51 98.12 96.65
[0095] Table 6 Oil retention rate of the cage at different times at 3000r / min in Example 2 (PAO10 lubricating oil)
[0096] 0min 10min 20min 30min 40min 50min 60min PPI cage 100 94.42 90.17 83.8 83.56 82.61 81.38 GPPI Cage 100 96.65 95.29 93.43 92.67 91.6 90.75
[0097] Depend on Fig.10 From Table 5, we can see that at 3000r / min, the oil retention rate of the GPPI cage is 96.65%, while the oil retention rate of the PPI cage is 94.42%. Fig.11 As shown in Table 6, after 60 min of sway at 3000 r / min, the oil retention rate of the GPPI cage is still higher than 90%, while that of the PPI cage drops to 81.38%.
[0098] Test Example 4
[0099] The only difference from Test Example 3 is that the PAO10 lubricating oil is replaced by the PAO4 lubricating oil.
[0100] The test results are shown in Tables 7 and 8. The data units in Tables 7 and 8 are %.
[0101] Table 7 Oil retention rate of the cage of Example 2 at different speeds (PAO4 Lubricating Oil )
[0102] 1000r / min 2000r / min 3000r / min PPI cage 95.11 94.25 90.00 GPPI Cage 98.25 97.72 95.06
[0103] Table 8 Oil retention rate of the cage at different times at 10000r / min in Example 2 (PAO4 lubricant)
[0104] 0min 10min 20min 30min 40min 50min 60min PPI cage 100 90.00 88.19 87.82 85.59 82.45 80.31 GPPI Cage 100 95.06 94.27 93.78 92.32 91.66 90.00
[0105] The test results show that the oil content of the PPI cage and the GPPI cage are 19.40% and 19.65% respectively. At 3000r / min, the oil retention rate of the GPPI cage is 95.06%, while the oil retention rate of the PPI cage is 90.00%. After 60 minutes of shaking at this speed, the oil retention rate of the GPPI cage is still higher than 90%, while the oil retention rate of the PPI cage drops to 80.31%.
[0106] Comparative Example
[0107] Omitting polar solvent immersion or carbon dioxide fluid immersion or high temperature treatment will not produce nanopores, and only the original porous cage morphology can be maintained, and a micro-nano multi-level porous polyimide cage cannot be obtained.
[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A micro-nano multi-level porous polyimide retainer, comprising mutually interpenetrating micropores and nanopores; the average pore diameter of the micropores is 1 to 3 μm, and the average pore diameter of the nanopores is 6 to 40 nm.
2. The micro-nano multi-level porous polyimide retainer according to claim 1, characterized in that: The porosity of the micro-nano multi-level porous polyimide retainer is 10-40%.
3. The method for preparing the micro-nano multi-level porous polyimide cage according to claim 1, characterized in that: The following steps are involved: The micron-sized porous polyimide cage is first immersed in a polar organic solvent to obtain a softened micron-sized porous polyimide cage; placing the softened micron-sized porous polyimide retainer in a carbon dioxide fluid environment for a second soaking, so that the carbon dioxide is dissolved in the retainer, thereby obtaining a micron-sized porous polyimide retainer in which carbon dioxide is dissolved; The micron-scale porous polyimide retainer with dissolved carbon dioxide is subjected to high-temperature treatment, the carbon dioxide gas expands to produce a nanoporous structure, and then cooled to obtain the micro-nano multi-level porous polyimide retainer; the temperature of the high-temperature treatment is 80-270°C.
4. The preparation method according to claim 3, characterized in that: The second immersion is performed at a temperature of 20 to 70° C., a pressure of 8 to 30 MPa, and a time of 0.5 to 72 h.
5. The preparation method according to claim 3, characterized in that: The high temperature treatment time is 10 to 120 seconds.
6. The preparation method according to claim 3, characterized in that: The polar organic solvent is one or more of N-methyl-2-pyrrolidone, dimethyl sulfoxide and N-N-dimethylacetamide.
7. The preparation method according to claim 3 or 6, characterized in that: The temperature of the first soaking is 25-150° C., and the time is 0.1-5 hours.
8. The preparation method according to claim 3, characterized in that: The average pore size of the micron-sized porous polyimide retainer is 1 to 3 μm.
9. The preparation method according to claim 3, characterized in that: Before the first soaking, the method further includes washing and drying the micron-sized porous polyimide retainer.
10. Use of the micro-nano multi-level porous polyimide cage according to claim 1 or 2 or the micro-nano multi-level porous polyimide cage prepared by the preparation method according to any one of claims 3 to 9 in low-speed bearings or high-speed bearings.
Citation Information
Patent Citations
Polyimide aerogel with micro-nano hierarchical pore distribution, and preparation method thereof
CN110358138A
High-molecular polymer foaming material as well as preparation method and application thereof
CN113462010A
Two-stage porous polyimide material, preparation method thereof, two-stage porous polyimide retainer and application of two-stage porous polyimide retainer
CN113510891A
Method for preparing rigid hierarchical porous block polyimide through supercritical carbon dioxide foaming
CN115782222A
Nanoporous microspherical polyimide aerogel and method for manufacturing the same
KR1020150117900A